Experimental Evaluation and Computer Analysis of Multi-Spiral Confinement in Reinforced Concrete Columns - Brubaker, Briana (Kansas State University, 2017)
Bridge and building construction in areas that sustain frequent seismic activity require the use of heavy lateral steel reinforcement within concrete columns to handle the lateral loads. Multi-spiral lateral reinforcement has been recently introduced to the construction field to offer an alternative to the traditional hoop and tie reinforcement. This report evaluates the experimental data observed in multiple experimental studies done on different concrete specimens. These specimens include multiple rectilinear reinforcement and several multi-spiral configurations in both rectangular and oblong columns. Due to multi-spiral reinforcement being a relatively new design, traditional computer programs have yet to include design analysis for this type of reinforcement in computer programs. Dr. Asad Esmaeily developed the program KSU RC 2.0 that can implement multiple analytical models to evaluate different multi-spiral configurations, as well as traditional hoop and tie confinement, that may be compared with experimental data. This report illustrates the comparative data from several different reinforced concrete column models. The data clearly indicates that multi-spiral reinforced columns exhibit higher compressive strength in the axial direction as well as higher ductility capabilities when compared to traditional rectilinear reinforcement of similar lateral steel reinforcement ratios. The use of multi-spiral reinforcement is also shown to lower costs for both the work time needed to install the structures as well as lowering the required steel ratio; all while maintaining the structural integrity of the columns.
Keywords: Multi-spiral reinforcement, Concrete column, Concrete confinement, Computer analysis